Pro Objective-C design patterns for iOS - Chung, Carlo (Apress, 2011)
It's time to capitalize on your mastery of Cocoa with Pro Objective-C Design Patterns for iOS. You've developed apps that impressed and performed, and now you're ready to jump into development practices that will leave you with more effective, efficient, and professional level apps. This book is the element you need to make the jump from journeyman to master. All too often, developers grind through building good apps on willpower and a vigorous focus on code development, leaving them unaware of and unable to benefit from the underlying structural and functional design patterns. Pro Objective-C Design Patterns for iOS will teach you those design patterns that have always been present at some level in your code, but were never recognized, acknowledged, or fully utilized. Implementation of specific pattern approaches will prove their value to any developer working in the iOS application arena. You'll learn to master classic patterns like singleton, abstract factory, chain of responsibility, and observer. You'll also discover less well-known but useful patterns like memento, composite, command, and mediator